The Effect Of Using Edmodo As Suplementary Class On Students’ Writing Achievement At SMKN 4 Kendari - Ariyanti, Firda; Hanna, Hanna; Amiruddin, Amiruddin (Halu Oleo University, 2017)
This study is aimed to find out whether there is significant effect of using edmodo as suplementary class on students’ writing achievement. This study used the pre-experimental design. The population was the 2016/2017 first year students of SMKN 4 Kendari, totally 413 students. The sample is 28 students from one class of textile design and production program (X KTC). The experimental group was taught by using Edmodo as suplementary class. The test was divided into two groups, pre-test and post- test. The instrument used in this study was a writing test. The data were analyzed by using paired sample t-test. The hyphotesis of this research was there was a significant effect of using Edmodo on students’ writing achievement at SMKN 4 Kendari (H1). The result of paired sample t-test shown that the asymp sig. is 0.000. It meant that the asymp sig. was lower than 0.05 (0.000 < 0.05). So, the H1 is unrejected. It could be concluded that using Edmodo has significant effect on students’ writing achievement at eleventh grade of Textile program (X KTC) in SMKN 4 Kendari.